THE IMPACT OF MOTIVATION AND WORK DISCIPLINE ON WORK EMPLOYEES PRODUCTIVITY - Suriyanti Suriyanti; Riski Eko Ardianto (Jurnal Ekonomi, 2023)
Competition in the business world is getting tougher today. Competition in the development of increasingly sophisticated knowledge anditechnology certainly brings changes to employee discipline. These changes resulted in higher job demands imposed on employees. In this study collected using the method of observation and questionnaires distributed to 87 respondents addressed to employees of Tenma Cikarang. This data collection uses multiple linear analysis to prove the research hypothesis. The data that has met the validity test, reliability test, and classical assumption test are then processed to obtain a regression equation. Based on the results oforesearch and discussion, it can be concluded that work motivation and work disipline affects work productivity, work motivation and work discipline simultaneously affect employee work productivity.